African Institute for economic development and planning - Economic Commission for Africa; Economic Commission for Africa, United Nations (Dakar, Senagal: Economic commission for Africa, 1970)
This book explains some of the administrative angle of the African institute for economic development and planning in Dakar.
asm; 28/02/19
Loans
Keywords: Economic development--Study and teaching; Africa